PEMANFAATAN SANITASI DAN BIOSEKURITI AREA PERKARANGAN RUMAH UNTUK MENCEGAH TERJADINYA DBD DI DESA COT MENTIWAN KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR - Alkautsar, Alkautsar; Yulia, Yara; Muddin, Ali; Sabarati, Sabarati (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health issue in Indonesia, including in Aceh Besar District. This research aims to analyze the effectiveness of sanitation utilization and biosecurity implementation in house yard areas for DHF prevention in Cot Mentiwan Village. The research employed a quasi-experimental method with pre-post intervention design involving 120 households selected through purposive sampling. The intervention consisted of education and assistance in environmental sanitation and yard biosecurity implementation for 3 months. Results showed significant decreases in larval density indices (House Index, Container Index, and Breteau Index) after intervention. The House Index decreased from 37.5% to 12.5% (p<0.001), Container Index decreased from 25.3% to 8.2% (p<0.001), and Breteau Index decreased from 52.5 to 16.7 (p<0.001). Significant improvements were also observed in community knowledge, attitudes, and practices related to DHF prevention efforts, as well as yard biosecurity implementation. The conclusion shows that utilizing sanitation and implementing biosecurity in house yard areas effectively prevents DHF. The research recommends sustainable implementation of this model integrated with the Mosquito Nest Eradication Program at the village level.